Handling child labor in Banda Aceh City: An analysis in optimizing stakeholder participation - Hanifa, Dina; Zamharira, Cut; Khalil, Zakki Fuad (Universitas Islam Negeri Ar-Raniry, 2024)
In Banda Aceh, it is common to see children who are not yet of working age selling in cafes and at traffic lights. Their working hours exceed 3 hours a day, and the work they do can threaten safety and interfere with children’s education, which is in conflict with law number 13 concerning employment. This study aims to determine stakeholder participation in handling child labor in Banda Aceh City. Employing qualitative research methods with a descriptive framework, researchers identified multiple actions undertaken by stakeholders in addressing child labor in Banda Aceh City. First, the Banda Aceh City Social Service has the authority to provide guidance to child workers. Second, DP3AP2KB Banda Aceh City has the authority to prevent and handle violence against children. Third, the UPTD PPA Banda Aceh City has the authority to respond quickly and is psychoeducational to child victims of violence. Fourth, Banda Aceh City Satpol PP and WH have the authority to supervise, control, and safeguard child workers to maximize public order and community security. Furthermore, the challenges in handling child labor in the City of Banda Aceh are: 1) the behavior of people who easily feel pity; 2) the behavior of child workers who are used to working on the streets; 3) the limited authority of the government; 4) weak applicable laws and no special regulations regarding child labor.